Shielded against risk? European donor co‐ordination in Palestine. (5th May 2021) - Orbie, Jan; Opsomer, Viktor; Williams, Yentyl; Delputte, Sarah; Verschaeve, Joren
Abstract: Motivation: There is a wide‐ranging consensus that co‐ordination in development policy is needed for aid effectiveness. However, our research reveals a number of surprising and significant gaps in existing scholarship. Development co‐ordination in Palestine has not been researched and the phenomenon of aid co‐ordination as "shielding" against domestic contestation remains underexamined. Purpose: This article aims to provide a better understanding of the "risk shielding" dynamic in European development co‐ordination through four case studies. It envisages theoretical insights on the "shield effect" and specifically: (a) how cracks may entail co‐ordination collapse; and (b) which conditions influence the continuation of such donor co‐ordination schemes. Approach and methods: The pragmatic and inductive research strategy is based on 74 expert interviews in Jerusalem and Ramallah in 2017 and 2019, which are triangulated with primary sources, existing evaluations, verification meetings and secondary literature. We examine four cases that vary in terms of successfulness. Coincidental variation between and within the cases allows us to infer theoretical insights. Findings: While donor co‐ordination in Palestine has often been pursued in order to shield against contestation, an opposite dynamic can also emerge whereby one donor succumbs to pressures and thereby contaminates the entire donor group. Our article provides an empirically grounded theorization of co‐ordination schemes' sustainability by identifying: (a) a five‐stage script of how domestic contestation may erode the shield; and (b) three conditions for sustainable co‐ordination. Finally, we make suggestions for further research, for instance from a politicization perspective. Policy implications: Before engaging in far‐reaching co‐ordination schemes, donors should consider the possible impact of domestic contestation within fellow donors and the creation of additional protective belts through international organizations. While donor consortia seem to be useful shields against attacks, they may put a heavy burden on all donors involved. Donors that are confident about domestic support should therefore consider going it alone. While Palestine constitutes a unique context, we expect that domestic contestation of aid will grow and hence that the "shielding" purpose will become increasingly relevant.